Colonial Anthropology: technologies and discourses of dominance 1886-1936 (London Routledge, 2024)
This book examines the process of domination of a civilization and the creation of a vast empire by the British in India in the late nineteenth and early twentieth centuries. It explores how they extended and maintained their tenuous rule over India through coercion, violent oppression, and exploration of knowledge of this vast region and its people.
Keywords: Asian Studies; Anthropology; History & Theory of Anthropology